Innovative Development and Investment Advancement of Industrial Enterprises in Deriving Conditions of Digital Economy - Dubyna, Maksym; Verbivska, Liudmyla; Shyshkina, Olena; Los, Andrii; Fediai, Yaroslav Fediai (Pacific Business Review (International), 2024)
In the article, features by implementing innovative development and investment advancement in the activities of industrial enterprises within the digitalized national economy are researched. It can be stated that digital technologies are of priority in the process of the business' entities development. These technologies greatly influence the functioning of industrial enterprises that also determine the innovative development level. As part of the study, the essence and features of innovative development and investment advancement as a separate economic category were analyzed, and features of economic activity of industrial enterprises being integral subjects of economic development of any country were specified. This made it possible to further substantiate the specific features of ensuring their innovative development and investment advancement. To substantiate modern development of industrial enterprises in digitalization era, the main challenges of digital economy facing today these business entities were determined. The outlined also made it possible to specify the features of their digital transformation. The impossibility to ensure innovative development and investment advancement of the modern industrial enterprise without implementing measures for its digital transformation is found out in the article. Based on this attention was also paid to specify the directions for the intensified potential use of digital technologies by industrial enterprises in modern conditions of their activity.
Innovative Development and Investment Advancement of Industrial Enterprises in Deriving Conditions of Digital Economy
Keywords: Digitization, Digital Economy, Industrial Enterprise, Digital Transformation, Innovative And Investment Development, Innovative Activity, Industry.